2013
DOI: 10.1016/j.neuropsychologia.2013.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormonal modulation of interhemispheric transfer time

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 72 publications
0
35
1
1
Order By: Relevance
“…&%! provided evidence that estradiol may also modulate interhemispheric interaction and, in turn, lateralisation (Hausmann et al, 2013, Weis et al, 2008Weis et al, 2011;Hausmann et al, 2006;Holländer et al, 2005). In line with this hypothesis, the reduced REA found in the non- Further analysis of the absolute LQs indicated that the reduction in the DL bias was mainly underpinned by estradiol.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…&%! provided evidence that estradiol may also modulate interhemispheric interaction and, in turn, lateralisation (Hausmann et al, 2013, Weis et al, 2008Weis et al, 2011;Hausmann et al, 2006;Holländer et al, 2005). In line with this hypothesis, the reduced REA found in the non- Further analysis of the absolute LQs indicated that the reduction in the DL bias was mainly underpinned by estradiol.…”
Section: Discussionmentioning
confidence: 52%
“…Hausmann et al, 2006) or estradiol alone (e.g. Hausmann, 2005;Holländer et al, 2005;Weis et al, 2008) that modulates the interhemispheric interaction between the left and right hemispheres (Hausmann et al, 2013;see Hausmann and Bayer, 2010 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings do however indicate that the menstrual cycle can affect the processing of rapid sequences in both hemispheres as reflected in the overall longer P1 latencies during the follicular phase. Latencies of early auditory (Tillman, 2010) and visual potentials (Hausmann et al, 2013) have been reported to vary during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this would result in a 'decoupling' of the hemispheres by reducing corticocortical transmission and interhemispheric inhibition (Hausmann & Güntürkün, 2000). This model was later revised, in light of evidence that estradiol may also modulate interhemispheric interaction and, in turn, lateralisation (Hausmann et al, 2013;Weis et al, 2008;Weis et al, 2011;Hausmann et al, 2006;Holländer et al, 2005). In line with this hypothesis, Hodgetts et al (2015) argued that the reduced REA found in women with high estradiol levels during the non-forced and forced- Given that interhemispheric inhibition is a universal process that should affect lateralisation generally, it follows that high estradiol levels should also reduce lateralisation for tasks related to the right hemisphere.…”
Section: Introductionmentioning
confidence: 99%